1999
DOI: 10.1159/000024268
|View full text |Cite
|
Sign up to set email alerts
|

Antigen–Specific, IgE–Selective Unresponsiveness Induced by Antigen–Liposome Conjugates

Abstract: Background: We have previously reported that ovalbumin (OVA) coupled with liposome via glutaraldehyde (GA) induced OVA–specific– and IgE–selective unresponsiveness in mice. Methods: In this study, OVA–liposome conjugates were made using four different coupling protocols: via GA, N–(6–maleimidocaproyloxy) succinimide (EMCS), disuccinimidyl suberate (DSS) and N–succimidyl–3(2–pyridyldithio)propionate (SPDP) and the induction of antigen–specific IgG and IgE antibody production was investigated for each. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
3
12
0
Order By: Relevance
“…We previously reported that surface-linked liposomal antigens induced IgEselective unresponsiveness [10]. The results were consistent even when different procedures for coupling antigens with liposomes [11], or for producing liposomes with different lipid components [12], were employed. During the course of an investigation intended to clarify the mechanism of IgEselective unresponsiveness induced by surface-coupled liposomal antigens, we discovered an alternative approach to regulating the production of IgE, one that is independent of the activity of T cells [13].…”
Section: Introductionsupporting
confidence: 70%
“…We previously reported that surface-linked liposomal antigens induced IgEselective unresponsiveness [10]. The results were consistent even when different procedures for coupling antigens with liposomes [11], or for producing liposomes with different lipid components [12], were employed. During the course of an investigation intended to clarify the mechanism of IgEselective unresponsiveness induced by surface-coupled liposomal antigens, we discovered an alternative approach to regulating the production of IgE, one that is independent of the activity of T cells [13].…”
Section: Introductionsupporting
confidence: 70%
“…Coupling procedure of antigens with liposomes was further investigated (15). OVA-liposome conjugates were generated using four different coupling protocols: GA (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon was consistently observed regardless of the particular antigen coupled to the liposomes [24, 25], the lipid components of the liposomes [26], or the procedure for coupling the antigen and the liposome [27]. Antigen-specific, IgE-selective unresponsiveness was induced by antigen-liposome conjugates only when antigen and liposomes were chemically coupled [28].…”
Section: Discussionmentioning
confidence: 99%